Re-think and act: Experience of the University Nutrition Education and Care Program (PREANU) of the University of Costa Rica in the context of the COVID-19 crisis, period 2020-2021 (Cuadernos de Extensión Universitaria de la UNLPam, 2022)
It reflects on the experience of the University Nutrition Education and Care Program of the University of Costa Rica, in response to the context of the crisis caused by COVID-19, the learning and challenges given the health emergency, the new socioeconomic needs and the growth of the population. food and nutritional insecurity in the population, for which a prompt university response is demanded. New topics and approaches were identified, and the adaptation or creation of new methodologies and tools due to the virtualization of work. Among the challenges and challenges are the limited resources for the sustainability of actions and innovation, as well as alliances with other instances to provide timely and relevant support to vulnerable populations that presented, since before the pandemic, and then perhaps more, serious food problems. and nutritional factors that affect their health and well-being, with educational and technological gaps and fewer opportunities for development.
Keywords: nutrition; nutritional education; nutritional care; COVID-19